ACCOUNTANCY SYSTEM OF CASHOUT FLOW IN SPBU 74.911.53 PAREPARE - yuliana; Zubair, Kamal; Astuty, An Ras Try (Funds: Jurnal Ilmiah Akuntansi, Keuangan, dan Bisnis, 2023)
The application of a company's cash disbursement accounting system is very important because, by applying a cash disbursement accounting system, the company is able to monitor and control the course of the company's operating activities so that they can run as they should. This is why the application of a cash disbursement accounting system is so important for a company. Similarly, SPBU 74,911.53 Parepare is responsible for the implementation of a cash disbursement accounting system that is comprised of aspects that are closely related to one another. These elements include papers used, records used, associated functions, and internal controls. However, there are some components whose application does not comply with the currently accepted theory; hence, it is essential to carry out research and investigate the present system at SPBU 74,911.53 Parepare. This research makes use of qualitative methods and takes a phenomenological approach to the data collection process. Data reduction is the method of analysis that is carried out here. According to the findings of the analysis, the cash